A nonlinear relationship between systemic inflammation response index and short-term mortality in patients with acute myocardial infarction: a retrospective study from MIMIC-IV - Wang, Yufei; Chen, Hua (Frontiers in Cardiovascular Medicine, 2023)
Background: This investigation aimed to evaluate the efficacy of the Systemic Inflammatory Response Index (SIRI) in prognosticating short-term all-cause mortality among patients diagnosed with acute myocardial infarction (AMI) in the intensive care unit (ICU). Methods and Results: Clinical data were obtained from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. A total of 4,291 patients were included in the cohort. Results from multivariate regression analyses showed that the quartile of the natural logarithm of SIRI (ln-SIRI) was independently associated with mortality. Compared to patients in the first quartile (Q1), patients in the second quartile (Q2) and fourth quartile (Q4) were significantly associated with an increased risk of 30-day (HR = 2.031, 95% CI: 1.604~2.571, P <0.001 and HR = 1.703, 95% CI: 1.32~2.195, P < 0.001) and 90-day all-cause mortality (HR = 2.063, 95% CI: 1.68~2.532, P < 0.001 and HR = 1.788, 95% CI: 1.435~2.227, P < 0.001), which is consistent with the results of the Kaplan-Meier analysis and the results of multivariate regression analyses by classifying into 12 groups based on dodeciles of SIRI. Curve fitting showed a curvilinear relationship and further threshold saturation effects showed that, for 90-day mortality, each unit increased in ln-SIRI, when the ln-SIRI level is less than 2.9, the patient’s mortality increases by 23.2% (OR: 1.232; 95% CI: 1.111~1.367; P < 0.001); when the ln-SIRI is greater than 2.9 and less than 4.6, the patient’s mortality decreases by 44.4% (OR: 0.554; 95% CI: 0.392~0.789; P = 0.001); when ln SIR>4.6, the patient’s mortality increases by 24.7% (OR: 1.247; 95% CI: 1.108~1.404; P < 0.001). Moreover, the length of stay in the hospital was lower in patients in the third quartile (Q3) (coefficient: -1.999; 95% CI: -2.834 ~ -1.165, P < 0.001). The length of stay in the ICU was higher in patients in Q2 and Q4 (coefficient: 0.685;95% CI: 0.243~1.128; P = 0.0024 and coefficient: 0.989;95% CI: 0.528~1.451; P < 0.001). Furthermore, SIRI may outperform NLR in predicting short-term mortality. Conclusion: SIRI is an independent risk factor for 30- and 90-day mortality, and length of stay in ICU for critical AMI patients.